2021
DOI: 10.1177/09697330211003269
|View full text |Cite
|
Sign up to set email alerts
|

Clinical ethics committees in nursing homes: what good can they do? Analysis of a single case consultation

Abstract: Background: Ought nursing homes to establish clinical ethics committees (CECs)? An answer to this question must begin with an understanding of how a clinical ethics committee might be beneficial in a nursing home context – to patients, next of kin, professionals, managers, and the institution. With the present article, we aim to contribute to such an understanding. Aim: We ask, in which ways can clinical ethics committees be helpful to stakeholders in a nursing home context? We describe in depth a clinical eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In China, more than 270,000 new cases are reported each year, making it the number one cancer for women and the sixth leading cause of death for women. Studies show that by 2050, 3.2 million people worldwide will be diagnosed with breast cancer each year [ 1 ]. The incidence rate and mortality rate of breast cancer in China are lower than the world average.…”
Section: Introductionmentioning
confidence: 99%
“…In China, more than 270,000 new cases are reported each year, making it the number one cancer for women and the sixth leading cause of death for women. Studies show that by 2050, 3.2 million people worldwide will be diagnosed with breast cancer each year [ 1 ]. The incidence rate and mortality rate of breast cancer in China are lower than the world average.…”
Section: Introductionmentioning
confidence: 99%
“…Both staff and top-level managers might expect them to handle and decide on challenges and value conflicts. Considering these expectations and responsibilities the CEC might be a particularly welcome support for this group (Magelssen & Karlsen, 2021).…”
Section: Several Services and Professions Are Absentmentioning
confidence: 99%
“…Clients in elderly services are often afflicted with multiple illnesses and health conditions affecting their functional abilities. In the case of elderly individuals with cognitive impairments, ethical questions linked to autonomy are accentuated (Bozzaro et al, 2018 ; Magelssen & Karlsen, 2022 ; Marks et al, 2021 ; Podgorica et al, 2021 ). Previous studies have also shown that conflicts around patient autonomy are especially prominent in home care (Heggestad et al, 2021 ; Lindberg et al, 2023 ; Öresland et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%